(untitled) (REMUNOM, 2024)
In recent years, digital transformation in public management has become a global priority, aiming to modernize processes and improve service delivery. Although governments are adopting digital platforms to make services more accessible and centered on citizens’ needs, there is a discrepancy between public expectations and the reality of implemented initiatives. Citizens demand more transparent, agile, and personalized public services but often face challenges such as lack of accessibility and digital bureaucracy. This article aims to identify the gaps between citizens’ expectations and government practices in digital transformation. To achieve this, a literature review on the subject will be conducted, followed by an analysis of the identified needs. Furthermore, examples of successful initiatives in Brazil will be presented, along with suggestions for improvements to increase citizen participation in the design and implementation of digital services.